MARKETABLE SURPLUS GABAH DI KECAMATAN LEBONG SAKTI KABUPATEN LEBONG PROVINSI BENGKULU - Zuhriati, Zuhriati; Utama, Satria Putra; Reswita, Reswita (Jurnal AGRISEP, 2014)
The objectives of this study are to identify the farmers’ characteristics in marketable surplus of paddy context in Lebong Sakti District; to estimated the rate of marketable surplus of paddy in Lebong Sakti District; and to their with influenced factors of marketable surplus of paddy in Lebong Sakti District. The respondent so were byselected using simple random sampling with the total 70 farmers. Statistical analysis used in this study was multiple linear regression analysis with Ordinary Least Square. Based on the result of the study and discussion, in average the age of the farmers is 43.94 years old, the level of formal education was 9.16 year while 3.74 for non-formal times a year, experience in paddy farming was 14.94 years, the number of family member was 4 people, income from non paddy shell field farming was Rp 3,301,240.00 and the field area for paddy shell field farming was 0.86 Ha. The percentage of marketable surplus of paddy was 31.85% of total production. While for Non-real, the percentage of marketable surplus of paddy was 3.25% of total production in. Total production and ownership status factory had a positive influence toward marketable surplus of paddy while number of family member had a negative influence to marketable surplus of paddy.